PENGARUH ETIKA FRONTLINER TERHADAP KENYAMANAN NASABAH di PERBANKAN SYARIAH KOTA - ERDAH, ERDAH LITRIANI; LEMIYANA, LEMIYANA LEMIYANA (I-Economics, 2016)
This study aims to determine the influence of ethic frontliner to the convenience of customer syariah banking at Palembang city. The sampling methods simple random sampling and the determination of the amount calculate dusing the formula Slovin. To 99 customers, branchis selected as a sample and then data were analyzed using multiple linear regression analysis. The results showed that ethic frontliner influence to the convenience of customers.KeyWord:ethic,front liner, convenience of customers